Studies on Shelf Life Extension of Chilgoza (Pinus gerardiana) - Abdul Haq, Muhammad; Hasnain, Abid (Asian Journal of Chemistry, 2012)
Chilgoza, specie of genus Pinus (pine nuts) is native to the Northwestern Himalaya. They are extracted from pine coats. The unshelled form has very short shelf life, which is an obstacle in its trade. An effort was made to retard the oxidation of these nuts using phenolic antioxidant; butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT). The antioxidants were delivered using two different polysaccharides based coatings; carboxymethyl cellulose (CMC) and gum cordia. Coated and control pine nuts were stored at 35 ºC and evaluated for 112 days every after 14 days. Gum cordia was found better than carboxymethyl cellulose to deliver the antioxidants. Gum cordia based coating in combination with BHA/BHT exhibited highest protection (165 % higher shelf life than control) based on peroxide value (20 meq.O2 kg-1) followed by gum codia plus BHT (125 %), gum cordia plus BHA (120 %), CMC plus BHA/ BHT (74%), CMC plus BHA (43 %) and CMC plus BHT (27 %).